FIGURATIVE LANGUAGE ON A WATTPAD NOVEL TEMPTING CURSE BY MSFOLLE - Alya Nadhilah Hutagalung (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2023)
This study contains the figurative language found in the novel Tempting Curse and the explanations of the meaning of these figurative languages. The researcher chose this study because the researcher felt that the figurative language in many novels sometimes made the readers cannot understand about figurative languages they read. So that this research is expected to help the readers understand the meaning of the figurative languages. For this study, the researcher used the theory from Montgomery et al (2007) as the basis for researching the types of figurative language studied. The research method used was semantic analysis. The results of this figurative language analysis research are found five types of the seven types of figurative language according to the theory of Montgomery et al (2007), namely metaphor, metonymy, simile, apostrophe, and irony. From the analysis, the researcher concludes that figurative language is used by the author only to beautify her writing and provide additional information on the phenomena that occur or the feelings experienced by the characters in detail.